2003
DOI: 10.1256/qj.02.76
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of NAO teleconnection pattern growth and decay

Abstract: SUMMARYThis investigation performs both diagnostic analyses with NCEP/NCAR re-analysis data and forced, barotropic model calculations to examine the dynamical mechanisms associated with the growth and decay of the North Atlantic Oscillation (NAO) teleconnection pattern. The diagnostic calculations include projection and composite analyses of each term in the stream-function-tendency equation.The results of the analyses reveal a complete life cycle of growth and decay within approximately two weeks. The positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
214
4
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(244 citation statements)
references
References 42 publications
22
214
4
2
Order By: Relevance
“…Feldstein (2003), Benedict et al (2004), Franzke et al (2004), and Riviere and Orlanski (2007) found that the NAO is breaking and the low-frequency/high-frequency eddies' breaking plays a fundamental role in the transition of the NAO phase. Our results here show that not only…”
Section: Discussionmentioning
confidence: 99%
“…Feldstein (2003), Benedict et al (2004), Franzke et al (2004), and Riviere and Orlanski (2007) found that the NAO is breaking and the low-frequency/high-frequency eddies' breaking plays a fundamental role in the transition of the NAO phase. Our results here show that not only…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Orsolini et al (2008) have recently analyzed the formation and life cyclone of the Aleutian-Icelandic Low Seesaw in an atmospheric GCM with a well resolved stratosphere, and they identified a clear extension of this Seesaw into the stratosphere, where its presence modulates the polar night jet intensity. Feldstein (2002Feldstein ( , 2003 investigated the nature of both PNA and NAO modes and concluded that the most important difference is that while PNA life cycle is dominated by linear processes, the variability of the NAO is dominated by nonlinear processes. Further, and unlike the PNA, the NAO may be interpreted as a forced phenomenon (Feldstein 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The NAO not only affects the surface temperature and the occurrence of storms and precipitation over the Europe, but also influences the global climate (Hurrell 1995a). Although the NAO is found to exhibit remarkable decadal variability (Hurrell 1995a;HĂ€kkinen 2000), the inherent time scale of the NAO events is actually about two weeks and the synopticscale eddies may be the dynamical driver of the NAO (Feldstein 2003). In a previous paper (Luo et al 2007, hereafter LLW), a weakly nonlinear model is proposed to account for the interaction between preexisting planetary-scale and synoptic-scale waves leads to an NAO event, a zonally localized dipole mode (Hurrell 1995b;Vallis et al 2004;Cash et al 2005).…”
Section: Introductionmentioning
confidence: 99%